The role of foreign aid in the transformation of Iraq's society and economy - Hadi Jaber (International Journal of Management and Economics, 2022)
Foreign aid helps in transforming nations and ensuring that they attain economic development. Foreign aid levels in Iraq are higher than those of its oil-producing neighbors due to numerous factors that are discussed in the present study. Iraq is the second largest oil producer in the Middle East after Saudi Arabia, but some activities within the country have curtailed development, leaving it at the mercy of foreign nations and investors. The present study aims to evaluate the level of foreign aid in Iraq, comparing it to its oil-rich neighbors. It highlights various factors that have increased Iraq's dependence on foreign aid and the role and management of this assistance. The article shows how negative factors like war, poor governance, and corruption have contributed to the over-reliance on foreign aid, in spite of Iraqbeing endowed with natural resources. The qualitative evaluation of the development of Iraq's oil aid reveals that continued reliance on foreign aid will jeopardizes the country's economic development.
Keywords: F35; O19; 650; foreign aid; Iraq; MENA; neighbors; OECD